2020
DOI: 10.3389/fbioe.2020.571993
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Platelets as an Oxygen Regulator for Augmenting Starvation Therapy Against Hypoxic Tumor

Abstract: The restriction of a tumor’s energy supply is proven to be an effective means of treatment. Glucose oxidase (GOx), an enzyme that catalyzes the conversion of glucose to glucolactone, producing oxygen and hydrogen peroxide in the process, has proved useful in this regard. However, hypoxia, which is implicated in tumor growth, has been found to mediate resistance to this type of tumor starvation. Here, we describe the design and testing of a platelet membrane mimetic, PMS, consisting of mesoporous silica nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Tumor growth was partially suppressed by MT or low-dose RT (2 Gy) in isolation, while high-dose RY (6 Gy) achieved more pronounced antitumor efficacy, and maximal efficacy was observed in the MT + low-dose RT group, consistent with the radiosensitizing activity of MT (Figures 3B,C). No animals exhibited any significant body weight changes over the course of the study, consistent with a lack of nonspecific treatmentrelated toxicity (Figure 3D), which is of particular importance as many similar therapeutic approaches have been linked to systemic adverse events (Huang et al, 2020b). TUNEL and Ki-67 staining of tumors collected from these mice similarly confirmed that combination MT + RT treatment was linked to pronounced necrosis and apoptosis within tumors and a concomitant loss of tumor tissue (Figure 3E).…”
Section: Resultssupporting
confidence: 58%
“…Tumor growth was partially suppressed by MT or low-dose RT (2 Gy) in isolation, while high-dose RY (6 Gy) achieved more pronounced antitumor efficacy, and maximal efficacy was observed in the MT + low-dose RT group, consistent with the radiosensitizing activity of MT (Figures 3B,C). No animals exhibited any significant body weight changes over the course of the study, consistent with a lack of nonspecific treatmentrelated toxicity (Figure 3D), which is of particular importance as many similar therapeutic approaches have been linked to systemic adverse events (Huang et al, 2020b). TUNEL and Ki-67 staining of tumors collected from these mice similarly confirmed that combination MT + RT treatment was linked to pronounced necrosis and apoptosis within tumors and a concomitant loss of tumor tissue (Figure 3E).…”
Section: Resultssupporting
confidence: 58%
“…A number of nanosystems carrying GOx have been synthetized to enhance ST by avoiding hazardous side effects and preventing degradation by proteinases. 42–44 To ensure long-lasting catalytic activity, Yang et al devised a nanovehicle to load GOx coordinated with folic acid and Zn 2+ termed GOx@PDA. 45 The nanodrug was further modified with a polydopamine (PDA) shell.…”
Section: Monotherapy Targeting Glucose Metabolismmentioning
confidence: 99%
“…In contrast to these oxygen supply-based strategies, Zhang et al instead developed an O 2 economizer that suppressed cellular respiration, thereby increasing oxygen availability for PDT or other relevant applications. Tumors, however, are heterogeneous, with many tumor tissues not exhibiting hypoxia. Many of these experimental systems designed to treat intratumoral hypoxia do not exhibit specific targeting to hypoxic tissue sites, which are commonly found deep within the core of tumor tissues. Traditional nanocarriers are generally unable to efficiently penetrate these deep tissue sites, limiting their therapeutic utility. There is thus an urgent need for the development of a hypoxia-specific tumor therapeutic platform that can bolster intratumoral oxygen levels and enhance PDT efficacy.…”
Section: Introductionmentioning
confidence: 99%